Radiation measurements at the German antarctic Neumayer Station - Wuttke, Sigrid; Seckmeyer, Gunther; Schrems, Otto; König-Langlo, Gert; Bernhard, Germar; Slusser, James R.; Herman, Jay R.; Gao, Wei (Bellingham Wash. : SPIE, 2005)
During the austral summer 2003/04 the Institute for Meteorology and Climatology, University of Hannover, Germany, has deployed a newly developed spectroradiometric system at the permanent German Antarctic Neumayer Station (70° 39' S, 8° 15' W). Aim of this campaign was to characterize the solar radiation conditions in an Antarctic environment. These are different from other areas of the Earth due to extremely high reflection of the ground (albedo). Relatively low cloud optical depths and ozone depletion further contribute to rather different radiation conditions compared to mid-latitudes. The investigation of these conditions will improve the understanding of the impact of climate change and ozone depletion in polar regions. Spectral irradiance and radiance as well as luminance and spectral albedo have been measured in a wavelength range from 280 to 1050 nm. With this set of radiation parameters it is assured that directional information of incident radiation parameters as well as the impact of surface albedo can be investigated. Monitoring of radiation parameters is carried out by the Alfred Wegener Institute for Polar and Marine Research, Bremerhaven, Germany. Spectral irradiance from 290 to 400 nm has been measured since January 2001. UVB monitoring started in 1997. Broadband radiation parameters have been detected since 1981. Furthermore, the station participates in international networks initiated by the Word Climate Research Programme such as the Baseline Surface Radiation Network (BSRN) and the Global Atmospheric Watch (GAW). It is also a complementary site of the Network for the Detection of Stratospheric Change (NDSC).